A traditional trace in the urban fabric: Architectural analysis of the Maltepe Mosque - Necdet Bekirhan Soy; Murat Karademir (Journal of Design for Resilience in Architecture and Planning)
This study aims to present an evaluation of contemporary mosque architecture by addressing the Maltepe Mosque in Ankara, which was built with a traditional approach. In Turkey, modern mosque architecture often adopts design approaches that aim to maintain the traces of the past and remain loyal to the local cultural identity. However, this sometimes causes traditional elements to become an obstacle to innovative architectural approaches. In the study, the architectural features of the Maltepe Mosque, the traditional elements used and the relationship of these elements with modern architecture will be analyzed. In particular, how key architectural elements such as the dome, minaret, mihrab and minbar, which are fundamental to Ottoman and Seljuk architecture, were used in this building and how they were integrated with modern construction techniques will be examined through the plan and structural elements of the mosque. The Maltepe Mosque was selected as a case study in order to question the place of traditional mosque architecture within modern urban life and architectural understanding, to discuss issues of aesthetics, functionality, and originality through architectural elements, and to provide a critical perspective on the future of mosque architecture in Turkey. Whether the design of the Maltepe Mosque, enriched with traditional elements, contributes to the creation of a contemporary structure, its integration with the urban fabric and the degree to which it meets the needs of the users are among the focal points of this study. The limitations imposed by traditionalist approaches in the mosque architecture in the context of modern architecture will be evaluated in terms of aesthetics, functionality and originality. The relationship of the building with its surroundings and the sustainability of traditional mosque forms in a modern city will also be addressed within this framework. Finally, the study aims to offer a unique perspective on the harmony of traditional architecture with modern architecture in Turkey, specifically in the Maltepe Mosque. While the repetition of traditional patterns in mosque architecture can be seen as a factor that limits creativity, it can also be considered as a meaningful step towards preserving collective memory. Therefore, the aim of this study is to critically evaluate this balance between the traditional and the modern and to offer ideas on how mosque architecture in Turkey may evolve in the future.